Comment on “exposure to microplastics (<10 μm) associated to plastic bottles mineral water consumption: The first quantitative study by Zuccarello et al. [Water Research 157 (2019) 365–371]” - Oßmann, Barbara; Schymanski, Darena; Ivleva, Natalia P.; Fischer, Dieter; Fischer, Franziska; Dallmann, Gerald; Welle, Frank (Water Research, 2019)
Microplastics in food is a relatively new research field with only few studies available so far. Scientists have been pointing out that some of these studies apply questionable analytical methods. Nevertheless, media often use such results to gain attention of the readers. It is therefore of particular significance, that only those scientific studies are published, clearly presenting valid data on the content of microplastics in food. Unfortunately, the study by Zuccarello et al. shows very critical aspects regarding analytical methods used and conclusions made. The applied procedure is not described and, therefore, does not allow any assessment by other groups, which is indispensable prerequisite of any scientific publication. Moreover, the analytical method used for the identification and quantification of microplastic particles – SEM-EDX – is not sound and not validated. Therefore, in our opinion the results on the contamination of bottled mineral water with microplastics published by Zuccarello et al. are more than questionable.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Bottled mineral water; Microplastics; PET bottles

Comment on "Plastic Teabags Release Billions of Microparticles and Nanoparticles into Tea" - Busse, Kristin; Ebner, Ingo; Humpf, Hans Ulrich; Ivleva, Natalia; Kaeppler, Andrea; Oßmann, Barbara; Schymanski, Darena (Environmental Science & Technology, 2020)
CRIS-Team Scopus Importer:2020-11-13

Correlative Microscopy and Spectroscopy Workflow for Microplastics - Sarau, George; Kling, Lasse; Oßmann, Barbara; Unger, Ann Katrin; Vogler, Frank; Christiansen, Silke H. (Applied spectroscopy, 2020)
Microplastics (MPs) have been reported in various environmental compartments and their number is continuously increasing because of degradation into smaller fragments down to nanoplastics. Humans are exposed to these small-sized MPs through food and air with potential health consequences that still need to be determined. This requires, in the first place, efficient and detailed visualization, relocalization, and characterization of the same MPs with complementary analytical methods. Here, we show the first application of a correlative microscopy and spectroscopy workflow to MPs that meets these demands. For this purpose, standard MP particles on aluminum-coated polycarbonate membrane filters were investigated by an optical zoom microscope and a hyphenated scanning electron microscopy (SEM)-Raman system. By merging the obtained data in one software, it is possible to navigate on the entire filters’ surface and correlate at identical locations MP morphology at the spatial resolutions of electron (1.6 nm at 1 kV for the used SEM, ∼100 nm minimum MP size in this study) and optical (∼1–10 µm) microscopies with chemical identification by micro-Raman spectroscopy. Moreover, we observed that low-voltage SEM works without a conductive coating of MPs, causes no detectable charging and structural changes, and provides high-resolution surface imaging of single and clustered MP particles, thus enabling subsequent Raman measurements. We believe that further work on the accurate identification and quantification of micro- and nanoplastics in real samples can potentially profit from this workflow.
CRIS-Team Scopus Importer:2020-08-14
Keywords: correlative workflow; Microplastic; microscopy; nanoplastic; Raman; scanning electron microscopy; SEM; spectroscopy

Critical Assessment of Analytical Methods for the Harmonized and Cost-Efficient Analysis of Microplastics - Primpke, Sebastian; Christiansen, Silke H.; Cowger, Win; De Frond, Hannah; Deshpande, Ashok; Fischer, Marten; Holland, Erika B.; Meyns, Michaela; O'Donnell, Bridget A.; Oßmann, Barbara; Pittroff, Marco; Sarau, George; et al. (Applied Spectroscopy, 2020)
Microplastics are of major concerns for society and is currently in the focus of legislators and administrations. A small number of measures to reduce or remove primary sources of microplastics to the environment are currently coming into effect. At the moment, they have not yet tackled important topics such as food safety. However, recent developments such as the 2018 bill in California are requesting the analysis of microplastics in drinking water by standardized operational protocols. Administrations and analytical labs are facing an emerging field of methods for sampling, extraction, and analysis of microplastics, which complicate the establishment of standardized operational protocols. In this review, the state of the currently applied identification and quantification tools for microplastics are evaluated providing a harmonized guideline for future standardized operational protocols to cover these types of bills. The main focus is on the naked eye detection, general optical microscopy, the application of dye staining, flow cytometry, Fourier transform infrared spectroscopy (FT-Ir) and microscopy, Raman spectroscopy and microscopy, thermal degradation by pyrolysis–gas chromatography–mass spectrometry (py-GC-MS) as well as thermo-extraction and desorption gas chromatography–mass spectrometry (TED-GC-MS). Additional techniques are highlighted as well as the combined application of the analytical techniques suggested. An outlook is given on the emerging aspect of nanoplastic analysis. In all cases, the methods were screened for limitations, field work abilities and, if possible, estimated costs and summarized into a recommendation for a workflow covering the demands of society, legislation, and administration in cost efficient but still detailed manner.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Fourier transform infrared spectroscopy; FT-IR; guideline; harmonization; microplastic; microscopy; nanoplastic; py-GC-MS; pyrolysis–gas chromatography–mass spectroscopy; Raman; Regulation; visually

Development of an optimal filter substrate for the identification of small microplastic particles in food by micro-Raman spectroscopy - Oßmann, Barbara; Sarau, George; Schmitt, Sebastian W.; Holtmannspoetter, Heinrich; Christiansen, Silke H.; Dicke, Wilhelm (Analytical and Bioanalytical Chemistry, 2017)
When analysing microplastics in food, due to toxicological reasons it is important to achieve clear identification of particles down to a size of at least 1 extgreekmm. One reliable, optical analytical technique allowing this is micro-Raman spectroscopy. After isolation of particles via filtration, analysis is typically performed directly on the filter surface. In order to obtain high qualitative Raman spectra, the material of the membrane filters should not show any interference in terms of background and Raman signals during spectrum acquisition. To facilitate the usage of automatic particle detection, membrane filters should also show specific optical properties. In this work, beside eight different, commercially available membrane filters, three newly designed metal-coated polycarbonate membrane filters were tested to fulfil these requirements. We found that aluminium-coated polycarbonate membrane filters had ideal characteristics as a substrate for micro-Raman spectroscopy. Its spectrum shows no or minimal interference with particle spectra, depending on the laser wavelength. Furthermore, automatic particle detection can be applied when analysing the filter surface under dark-field illumination. With this new membrane filter, analytics free of interference of microplastics down to a size of 1 extgreekmm becomes possible. Thus, an important size class of these contaminants can now be visualized and spectrally identified.
EAM Import::2019-03-13

Small-sized microplastics and pigmented particles in bottled mineral water - Oßmann, Barbara; Sarau, George; Holtmannspötter, Heinrich; Pischetsrieder, Monika; Christiansen, Silke; Dicke, Wilhelm (Water Research, 2018)
Up to now, only a few studies about microparticle contamination of bottled mineral water have been published. The smallest analysed particle size was 5 gm. However, due to toxicological reasons, especially microparticles smaller than 1.5 mu m are critically discussed. Therefore, in the present study, 32 samples of bottled mineral water were investigated for contamination by microplastics, pigment and additive particles. Due to the application of aluminium coated polycarbonate membrane filters and micro-Raman spectroscopy, a lowest analysed particle size of 1 mu m was achieved.Microplastics were found in water from all bottle types: in single use and reusable bottles made of poly(ethylene terephthalate) (PET) as well as in glass bottles. The amount of microplastics in mineral water varied from 2649 +/- 2857 per litre in single use PET bottles up to 6292 +/- 10521 per litre in glass bottles. While in plastic bottles, the predominant polymer type was PET; in glass bottles various polymers such as polyethylene or styrene-butadiene-copolymer were found. Hence, besides the packaging itself, other contamination sources have to be considered.Pigment particles were detected in high amounts in reusable, paper labelled bottles (195047 +/- 330810 pigment particles per litre in glass and 23594 +/- 25518 pigment particles per litre in reusable paper labelled PET bottles). Pigment types found in water samples were the same as used for label printing, indicating the bottle cleaning process as possible contamination route.Furthermore, on average 708 +/- 1024 particles per litre of the additive Tris(2,4-di-tert-butylphenyl) phosphite were found in reusable PET bottles. This additive might be leached out from the bottle material itself.Over 90% of the detected microplastics and pigment particles were smaller than 5 mu m and thus not covered by previous studies. In summary, this is the first study reporting about microplastics, pigment and additive particles found in bottled mineral water samples with a smallest analysed particle size of 1 mu m. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Microplastics; Pigments; Bottled mineral water; Micro-Raman spectroscopy; Food